2007
DOI: 10.3201/eid1306.060955
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Imported FatalPlasmodium falciparumMalaria, France, 1996–2003

Abstract: Plasmodium falciparum malaria is a serious health hazard for travelers to malaria-endemic areas and is often diagnosed on return to the country of residence. We conducted a retrospective study of imported falciparum malaria among travelers returning to France from malaria-endemic areas from 1996 through 2003. Epidemiologic, clinical, and parasitologic data were collected by a network of 120 laboratories. Factors associated with fatal malaria were identified by logistic regression analysis. During the study per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
31
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 28 publications
10
31
1
Order By: Relevance
“…ICU mortality (5.47 %) was close to previously reported rates [17, 21, 27, 28]. We found that adult mortality rates in MW and ambulatory care were 0.1 and 0.01 %.…”
Section: Discussionsupporting
confidence: 87%
“…ICU mortality (5.47 %) was close to previously reported rates [17, 21, 27, 28]. We found that adult mortality rates in MW and ambulatory care were 0.1 and 0.01 %.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, we found higher case fatality rates occurred in imported cases during January and February, which normally covers the Chinese New Year holidays. In this period, delayed presentation to medical services, lower levels of hospital staffing over the holiday period, and delays in communication of malaria diagnosis from laboratory to physician may be contributory factors, and other possibilities include initial misdiagnosis of a febrile illness as influenza-like illness in the winter-spring epidemic season728. Additionally, the fatal cases had a shorter median length of stay, which might relate to the severity of infection, healthcare-seeking behaviours, malaria prevention measures, individual immunity and the previous history of malaria, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Each year, 2, 200 imported malaria cases are reported to the French Malaria National Reference Center (FMNRC) among returned international travellers, and the real number of cases is estimated at 4, 000 [1]. Prompt diagnosis is essential for the treatment and outcome.…”
Section: Introductionmentioning
confidence: 99%